DISADVANTAGED NEIGHBORHOODS AND FEAR OF CRIME: - (:unkn) unknown (My University, 2010)
Fear of crime is a serious individual and community level problem, particularly in urban areas. A disadvantaged neighborhood with visual signs of disorder has been shown to increase fear of victimization. Disadvantaged neighborhoods are risky environments where the fear of being victimized is often valid and justified. The neighborhood conditions that make criminal victimization more or less likely could also contribute to higher levels of fear of crime. Research has linked such factors as low levels of guardianship and high levels of target attractiveness to greater risks of crime, which in turn leads to greater fears of victimization. Levels of guardianship can be measured by how integrated one feels within the community. Strong community integration, along with social bonds between the neighborhood and family, significantly reduce levels of fear.

Using data from the Project on Human Development in Chicago Neighborhoods (PHDCN), this research looks at the relationship between neighborhood disadvantage and fear of victimization, specifically whether family structure (i.e., living in a two-parent family) mediates the relationship between neighborhood disadvantage and fear of crime. The analyses found that while a number of individual-level and neighborhood-level variables were significant predictors of both fear of crime and perceptions of neighborhood safety, family structure was not among them; nor were there any significant interactions between the individual- and neighborhood-level variables.
Keywords: Fear of crime--Illinois--Chicago; Fear in children--Illinois--Chicago; Poor children--Family relationships--Illinois--Chicago; Children--Illinois--Chicago--Social conditions; Teenagers--Illinois--Chicago--Social conditions; Chicago (Ill.)--Social conditio